Hospital management preparedness tools in biological events: A scoping review - Mohsen Aminizadeh; Mehrdad Farrokhi; Abbas Ebadi; Gholam Reza Masoumi; Pirhossein Kolivand; Hamid Reza Khankeh (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: The objective of the present study was to systematically review the current research knowledge on hospital preparedness tools used in biological events and factors affecting hospital preparedness in such incidents in using a scoping review methodology. MATERIALS AND METHODS: The review process was conducted in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guideline. Online databases (PubMed, Scopus, Web of Science, and Google Scholar) were used to identify papers published that evaluated instruments or tools for hospital preparedness in biological disasters (such as influenza, Ebola, and bioterrorism events). The search, article selection, and data extraction were carried out by two researchers independently. RESULTS: A total of 3440 articles were screened, with 20 articles identified for final analysis. The majority of research studies identified were conducted in the United States (45%) and were focused on CBRN incident (20%), Ebola, infectious disease and bioterrorism events (15%), mass casualty incidents and influenza pandemic (10%), public health emergency, SARS, and biological events (5%). Factors that were identified in the study to hospitals preparedness in biological events classified in seven areas including planning, surge capacity, communication, training and education, medical management, surveillance and standard operation process. CONCLUSIONS: Published evidences of hospital preparedness on biological events as well as the overall quality of the psychometric properties of most studies were limited. The results of the current scoping review could be used as a basis for designing and developing a standard assessment tool for hospital preparedness in biological events, and it can also be used as a clear vision for the healthcare managers and policymakers in their future plans to confront the challenges identified by healthcare institutes in biologic events.